Mass Spectrometry Imaging in Nanomedicine: Unraveling the Potential of MSI for the Detection of Nanoparticles in Neuroscience - P.Y. Barre, Florian; M.A. Heeren, Ron; Ogrinc Potocnik, Nina (Current Pharmaceutical Design, 2017)
Mass spectrometry imaging (MSI) can uniquely detect thousands of compounds allowing both their identification and localization within biological tissue samples. MSI is an interdisciplinary science that crosses the borders of physics, chemistry and biology, and enables local molecular analysis at a broad range of length scales: From the subcellular level to whole body tissue sections. The spatial resolution of some mass spectrometers now allows nano-scale research, crucial for studies in nanomedicine. Recent developments in MSI have enabled the optimization and localization of drug delivery with nanoparticles within the body and in specific organs such as kidney, liver and brain. Combining MSI with nanomedicine has vast potential, specifically in the treatment of neurological disorders, where effective drug delivery has been hampered by the blood-brain barrier. This review provides an introduction to MSI and its different technologies, with the application of MSI to nanomedicine and the different possibilities that MSI offers to study molecular signals in the brain. Finally, we provide an outlook for the future and exciting potential of MSI in nanoparticle-related research.
Keywords: brain